ANALISIS PENGARUH PERCEIVED VALUE, PERCEIVED EASE OF USE DAN PERCEIVED USEFULNESS TERHADAP NIAT BELI KEMBALI SECARA ONLNE DI KOTA YOGYAKARTA - Ikhsani, Muatiara Nurul (Program Studi Manajemen Fakultas Ekonomi UST, 2025)
This study aims to analyze the influence of Perceived Value, Perceived Ease of Use, and Perceived Usefulness on Online Repurchase Intention among consumers in Yogyakarta City. The research is motivated by the growing use of e-commerce platforms, highlighting the need to understand the factors that influence consumer behavior in making repeat purchases. This quantitative study collected data through offline questionnaires distributed to 100 respondents who had made online purchases. The data were analyzed using multiple linear regression with the assistance of SPSS software. The results indicate that all three independent variables—Perceived Value, Perceived Ease of Use, and Perceived Usefulness—have a significant positive effect on Online Repurchase Intention. These findings provide practical implications for e-commerce businesses to enhance the perceived value, ease of use, and usefulness of their platforms in order to foster consumer loyalty. However, this study is limited in terms of geographic scope and sampling technique. Future research is recommended to broaden the sample population and incorporate other relevant variables.